¿De qué estamos hechos? (2018)
Memories are fragmented pieces of the past that have survived the misadventure of time and oblivion. Its purpose is to transform itself into a word, in order to re-pass through the heart what has already been lived, while the sigh that spreads between the pages of a notebook springs up. The participant's body remains static, and a magical moon with star petals begins to bloom in the eye sockets. Each tear harbors one of the stories that constitute its cosmos of memories, which when coming together and shine in unison, produces a beam of lights full of emotions capable of alleviating the thick fog that covers the existence. The purpose of these is fundamental in all this process of significance, since they contain flashes of madness and nostalgia maligned by deafening memories, capable of crossing the barrier of absence and oblivion. His strength is such that he will seek to rest on the bare sheet under a moonlight, while the pen surrenders to his passion drop by drop. The result will be cartographies that glimpse the passage of experience, leaving exposed dreams, desires and delusions, but also anguish, afflictions and anguish. These feelings, now transfigured in words, will be the blows of the chisel in the naked marble that will shape a new being. In this way, narratives emerge that open and cauterize wounds. Narratives that bleed silently. Narratives that preserve the essence of that being from which they sprang. Narratives that are the reflection of a being that lives, thinks and feels.